Mobile Robotics for Throughput Testing in a Reconfigurable Test Environment - Araújo, Eduardo; Miranda, Breno (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
The growing demand for wireless connectivity in applications such as the Internet of Things (IoT), autonomous vehicles, and industrial automation requires accurate performance evaluation of networks in mobile and dynamic environments. This work proposes the development of a reconfigurable test environment based on mobile robots, using Raspberry Pi Zero 2 W boards to periodically collect Wi-Fi signal data from different positions within a physical space. Two experimental scenarios are considered: (i) client mobility, in which a Mesh router is mounted on a robot that performs measurements while moving, while the Raspberry Pi remains stationary collecting data; and (ii) infrastructure mobility, in which Mesh routers mounted on robots move while the Raspberry Pi remains fixed, collecting data. Data collection is performed using native commands from the embedded Linux system, and results are stored in JSON files for later analysis. This approach directly evaluates signal degradation, connection instability, handover events, physical obstacles, and network fluctuations in realistic scenarios. The expected outcomes of our research include the creation of a valuable dataset for validating wireless connectivity quality and supporting the development of more robust solutions for mobile networks and dynamic environments. This work presents an innovative reconfigurable testbed combining mobile robots and automated diagnostics capable of accurately and reproducibly evaluating handover and latency in Wi-Fi Mesh networks.